Differences in Viral RNA Synthesis but Not Budding or Entry Contribute to the In Vitro Attenuation of Reston Virus Compared to Ebola Virus - Bianca S. Bodmer; Josephin Greßler; Marie L. Schmidt; Julia Holzerland; Janine Brandt; Stefanie Braun; Allison Groseth; Thomas Hoenen (Microorganisms, 2020)
Most filoviruses cause severe disease in humans. For example, Ebola virus (EBOV) is responsible for the two most extensive outbreaks of filovirus disease to date, with case fatality rates of 66% and 40%, respectively. In contrast, Reston virus (RESTV) is apparently apathogenic in humans, and while transmission of RESTV from domestic pigs to people results in seroconversion, no signs of disease have been reported in such cases. The determinants leading to these differences in pathogenicity are not well understood, but such information is needed in order to better evaluate the risks posed by the repeated spillover of RESTV into the human population and to perform risk assessments for newly emerging filoviruses with unknown pathogenic potential. Interestingly, RESTV and EBOV already show marked differences in their growth in vitro, with RESTV growing slower and reaching lower end titers. In order to understand the basis for this in vitro attenuation of RESTV, we used various life cycle modeling systems mimicking different aspects of the virus life cycle. Our results showed that viral RNA synthesis was markedly slower when using the ribonucleoprotein (RNP) components from RESTV, rather than those for EBOV. In contrast, the kinetics of budding and entry were indistinguishable between these two viruses. These data contribute to our understanding of the molecular basis for filovirus pathogenicity by showing that it is primarily differences in the robustness of RNA synthesis by the viral RNP complex that are responsible for the impaired growth of RESTV in tissue culture.